Petrology, petrogenesis and tectonic setting of plutonic rocks in the North Mountain area, west-central Cape Breton Island, Nova Scotia - Justino, Mario; Barr, Sandra (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1994)
The Marble Mountain area of west-central Cape Breton Island is underlain mainly by granitoid rocks of the Marble Mountain, Big Brook, and West Bay plutons, migmatitic gneisses of the Lime Hill gneissic complex, and low-grade metasedimentaiy rocks of the Malagawatch Formation. The Late Precambrian Marble Mountain and Big Brook plutons are composed of homblende-biotite tonalite to granodioritc. These plutons underwent similar but separate evolutionary histories involving fractionation of plagioclase and hornblende ± biotitc. They display penological similarities to Cordilleran I-type suites, as exemplified by the Peninsular Ranges Batholith, and are interpreted to have formed by partial melting of a mainly basaltic source, and to represent the root zone of a primitive volcanic arc at a convergent plate margin. In contrast, the West Bay Pluton consists of megacrystic monzogranite and associated, probably co-genetic, granitic porphyritic dykes. The pluton is a felsic granite with I-type mineralogy but displays evolutionary trends distinct from typical felsic I-, S-, and A-type granites. The tectonic setting is interpreted to be post-orogenic, and the magma may have formed by a high degree of partial melting of a mainly crust al source. The age of the West Bay Pluton is uncertain, but may be Early Ordovician, based on penological similarity to other granitic plutons in the Bras d'Or terrane which have yielded U-Pb (zircon) ages of ca. 495 Ma.